Socio-Economic Effects of Orisumbare Sawmilling Industries on The Residents of Ikire, Irewole Local Government Area Osun-State, Nigeria - Jimoh, Umar Usman; Ogungbemi, D R (UI Scholars Hub, 2024)
The study examined the socio-economic effects of the Orisumbare sawmill industry on the residents of Ikire, Irewole local government area of Osun State. The objectives of the study include, examination of the socio-economic characteristics of the respondents, the positive effects of industry on the residents, the negative impacts of industry on the residents, and the perceived environmental-induced diseases caused by industrial activities. A case study research design was adopted, while both primary and secondary data were utilised. A multistage sampling technique was used, in which a buffer zone of 900m radius was made to delineate the zone of industries’ influence. This was later stratified into three zones, and a household head found in each of the residential buildings within the zone was randomly selected. A questionnaire was administered to 261 household heads in the sampled buildings. The collected data were analysed using both descriptive and logistic regression. Orisumbare sawmill had a positive significant impact on the residents of Ikire (F = 0.858). Sawmill activities have a significant effect on the socio-economic lives of the residents. Cottage industries should be harnessed in order to explore their opportunities, since the resources are not fully utilised.